Sexual functioning after childhood abuse: the influence of post-traumatic stress disorder and trauma exposure - Bornefeld-Ettmann, Pia; Steil, Regina; Lieberz, Klara A.; Bohus, Martin; Rausch, Sophie; Herzog, Julia; Priebe, Kathlen; Fydrich, Thomas; Müller-Engelmann, Meike (The journal of sexual medicine, 2018)
Background - Impairments in sexual functioning and sexual satisfaction are very common in women who have experienced childhood sexual abuse (CSA). A growing body of literature suggests a high prevalence of sexual distress in patients with post-traumatic stress disorder (PTSD). However, the influence of sexual trauma exposure per se and the influence of PTSD symptoms on impairments in sexual functioning remain unclear. - Aim - The aim of this study was to investigate the influence of sexual trauma exposure and PTSD on sexual functioning and sexual satisfaction by comparing 3 groups of women. - Methods - Women with PTSD after CSA (N = 32), women with a history of CSA and/or physical abuse but without PTSD (trauma controls [TC]; N = 32), and healthy women (N = 32) were compared with regards to self-reported sexual functioning and sexual satisfaction. Trauma exposure was assessed with the Childhood Trauma Questionnaire, and PTSD was assessed with the Clinician-Administered PTSD Scale for Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition. - Outcomes - Sexual functioning was assessed with the Sexual Experience and Behavior Questionnaire, and sexual satisfaction was assessed with the questionnaire Resources in Sexuality and Relationship. - Results - PTSD patients had significantly lower sexual functioning in some aspects of sexual experience (sexual aversion, sexual pain, and sexual satisfaction) but did not significantly differ in sexual arousal and orgasm from the other 2 groups. TC and healthy women did not significantly differ from each other on the measures of sexual functioning or sexual satisfaction. - Clinical Translation - Results suggest that the development of PTSD has a greater impact on sexual functioning than does the experience of a traumatic event. This emphasizes the importance to address possible sexual distress and sexual satisfaction in women with PTSD by administering specific diagnostic instruments and by integrating specific interventions targeting sexual problems into a trauma-specific treatment. - Conclusions - The study is the first comparing PTSD patients and TC with healthy women with regards to sexual functioning. Limitations are selection and size of the samples, the assessment of sexual functioning by self-report measures only, and lack of consideration of other potentially relevant factors influencing sexuality. The findings suggest that the experience of sexual abuse does not necessarily lead to sexual impairment, whereas comparably low levels of sexual functioning seem to be prominent in PTSD patients after CSA. Further research is needed on how to improve treatment for this patient group. Bornefeld-Ettmann P, Steil R, Lieberz KA, et al. Sexual Functioning After Childhood Abuse: The Influence of Post-Traumatic Stress Disorder and Trauma Exposure. J Sex Med 2018;15:529-538.